The Effect of the Application of Brainstorming Learning Techniques on Student Learning Outcomes in History Subjects in Grade XI Social Studies Students - Santosa, Affan Budi (Universitas Negeri Semarang, 2018)
In the process of teaching and learning, teachers must have a strategy, so that students can learn effectively and efficiently, which is expected to hit the goal. One step to have a strategy that is to be mastered the techniques of presentation, students are expected to participate in the learning process history by boldly convey ideas in history, in order to create an active learning. To realize the historical quality of learning outcomes, can be applied learning techniques Brainstorming. The approach used in this thesis research is a quantitative approach, the design Quasi Experimental kind of pre-test and post-test control group design. The study population was students of class social science class with a total of 83 students are divided into four classes. The research sample using social science class as the control group and social science class as the experimental group. Using data from pre-test to test the equality of two variances before the treated group, followed by learning and ending with post-test.